A new 1D coordination polymer of lanthanum-sulfate-1,10-phenanthroline: Synthesis, structure, and photoluminescence property - Bunlawee Yotnoi (2018)
A 1D coordination framework, {[La2(o-phen)2(SO4)3(H2O)2]}n(1) (o-phen = 1,10-phenanthroline) was hydrothermally synthesized and characterized by single-crystal X-ray diffraction, elemental analysis, IR, and UV-Vis spectroscopy. The crystal of 1 crystallized in the triclinic P,1. space group, a = 10.3228(5) Å, b = 12.3644(7) Å, c = 12.6579(6) Å, α = 72.323(2)°, β = 75.610(2)°, γ = 82.785(2)°, V = 1488.82(13) Å3, Z = 2. The structure exhibits a neutral 1D framework representing a five-connected uninodal 1-periodic net of (3,6)(0,2) topology. The framework structure comprises TPRS-9 LaO7N2 units, chelating o-phen ligands and bridging sulfates of 3.1110 and 4.2211 coordination modes. These 1D chains are extended into a 3D supramolecular structure by hydrogen bonding interactions of, R22(n) patterns. Thermogravimetric analysis shows the structure to be thermally stable up to approximately 400°C. Photoluminescence investigations on Eu3+and Tb3+doped samples suggest the competition between the ligand-to-metal charge-transfer and energy-transfer processes. Copyright © Taylor & Francis Group, LLC.